Investing in Indonesia during the pandemic covid-19, it is safe? - Tuti Zakiyah; Wahyuni Windasari (INOVASI, 2022)
This study aims to prove the safety of investment in Indonesia during the covid-19 pandemic. By analyzes the dynamic correlation between gold, Composite Supply Price Index (CSPI), LQ45, and Sharia supply (JII) as a reference investment instrument that is a haven investment and has hedging during the COVID-19 pandemic in Indonesia. The sampling technique used is Saturated Sample. This research data is gold closing price data, closing (CSPI), and Closing Jakarta Islamic index (JII). The research period used during the COVID-19 pandemic is March 11, 2020, to December 31, 2020. This research method uses the Dynamic Conditional Correlation-Generalized Autoregressive Conditional Heteroskedasticity (DCC-GARCH) model with gold research results, CSPI, LQ 45. JII is a very safe asset. It is used as Asset Safe Haven and hedging to reduce investor losses or minimize the risk from investing, especially when there is market uncertainty or economist pressure during the Covid-19 Pandemic.